Parameter optimization of chemical reduction of graphene oxide using design expert - Mohamed, Syukri (2019)
Graphene or also known as reduced graphene oxide exhibit variety of fascinating properties. Due to many possibilities to be utilized in wide field of application, the researches in fabrication had been made. Chemical reduction of graphene oxide is one of the methods known in synthesizing graphene. Graphene oxide was synthesized by the oxidation of graphite by following modified Hummer’s method. In the reduction of graphene oxide, L-ascorbic was used as the reductant followed with addition of ammonia. This research was done optimize the reduction parameters (concentration of ascorbic acid, temperature and time of reduction reaction) to maximize the properties of reduced graphene oxide (rGO) using central composite design (CCD) from Design Expert® and to investigate the effect of chemical reduction of graphene oxide (GO) parameters towards the final properties of reduced graphene oxide (rGO) in term of phase composition, crystallinity, particle size and conductivity. The properties of rGO was characterized by undergoing different analysis which are crystalline structure analysis by XRD diffractometer, , zeta potential and particle size by Nano-ZS Zetasizer and finally the conductivity analysis by calculation of electrical conductivity of rGO suspension in deionized water. The optimum conditions of chemical reduction of GO are 17.612 mg/mL for the concentration of ascorbic acid, duration of 197.817 minutes at temperature 95 °C which predicted to result zeta potential of 16.70 mV in deionized water, has conductivity of 2.2 x10-2 S/m, particle size of 121.63 nm with interplanar spacing of 0.36 nm.